Az Ister-Granum Eurórégió fejlesztési stratégiái - Hartl, Mónika (Közép-Európai Közlemények, 2011)
In my research I am looking for the prominent opportunities of the Slovak-Hungarian border. I would like to stress that the development of the regional economy is absolutely necessary regarding the improvement of the tourism sector since it will create opportunities to retail local goods. In order to improve tourism it is also vital to have a high standard in infrastructure and in services. The border destinations can be very tempting for investing capital and in this way the multiplicator effect can be realised. I also examine the motivations to cross the border. I try to call attention how underused the euro region’s potentials are and that it is essential to form a unified tourism marketing and marketing communication. Developments, strategies: An inventory of the Euroregion has been completed with all of the conditions that are useful for tourism taken stock of. Village tourism, cultural tourism and spa tourism can all be branches of tourism developments building on the excellent conditions. They would like to popularise the natural and touristic values of the Euroregion in publications, professional forums and exhibitions.